2009
DOI: 10.1017/s0317167100007009
|View full text |Cite
|
Sign up to set email alerts
|

NeuroAIDS: An Evolving Epidemic

Abstract: Over 60,000 Canadians are infected with human immunodeficiency virus (HIV). Greater than 50% of these individuals will develop a neurological disorder despite the availability of highly active antiretroviral therapy. HIV causes nervous system disease at all stages of infection with adverse effects on quality of life, adherence to medications, employment and survival. These disorders include opportunistic infections in addition to distinct HIV-associated neurological syndromes and undesirable treatment-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 88 publications
0
44
0
Order By: Relevance
“…The occurrence of some neurologic disorders including HAD is correlated with the blood CD4ϩ T-cell levels. 4,17 Stratification of baseline CD4ϩ T-cell levels revealed that late-presenting patients who showed severe immune suppression (CD4ϩ T-cell levels Ͻ200 cells/mm 3 ) also exhibited higher prevalence of DSP, movement disorder, seizures/ epilepsy, and CNS-OIs compared with patients showing moderate or minimal immunosuppression ( p Ͻ 0.05, figure 2A). There was no difference in prevalence of neurologic disorders between patients with no (CD4ϩ T-cell levels Ͼ500 cells/mm 3 ) and moderate (CD4ϩ T-cell levels 200 -500 cells/mm 3 ) immunosuppression.…”
Section: Statistical Analysis Demographic Variables Of Interest Werementioning
confidence: 99%
“…The occurrence of some neurologic disorders including HAD is correlated with the blood CD4ϩ T-cell levels. 4,17 Stratification of baseline CD4ϩ T-cell levels revealed that late-presenting patients who showed severe immune suppression (CD4ϩ T-cell levels Ͻ200 cells/mm 3 ) also exhibited higher prevalence of DSP, movement disorder, seizures/ epilepsy, and CNS-OIs compared with patients showing moderate or minimal immunosuppression ( p Ͻ 0.05, figure 2A). There was no difference in prevalence of neurologic disorders between patients with no (CD4ϩ T-cell levels Ͼ500 cells/mm 3 ) and moderate (CD4ϩ T-cell levels 200 -500 cells/mm 3 ) immunosuppression.…”
Section: Statistical Analysis Demographic Variables Of Interest Werementioning
confidence: 99%
“…These may all contribute to encephalopathy, acute symptomatic seizures, and epilepsy (Mamidi et al, 2002;Power et al, 2009;Roullet, 1999).…”
Section: Human Immunodeficiency Virusmentioning
confidence: 99%
“…3e5 However, neurological complications of HIV infection still cause considerable morbidity and mortality, and >50% of the patients develop neurological disorders, even in the HAART era. 4,6,7 Because of its neurotropism, HIV can affect the CNS directly, inducing various neurological syndromes, including HIV-associated neurocognitive disorders, encephalitis and/ or meningitis, myelopathy and a high risk of seizures. 2,7,8 Studies conducted on critically ill patients showed that severe neurological complications were the third cause of ICU admission for HIV-positive patients, representing 10e20% of all ICU-admission diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…4,6,7 Because of its neurotropism, HIV can affect the CNS directly, inducing various neurological syndromes, including HIV-associated neurocognitive disorders, encephalitis and/ or meningitis, myelopathy and a high risk of seizures. 2,7,8 Studies conducted on critically ill patients showed that severe neurological complications were the third cause of ICU admission for HIV-positive patients, representing 10e20% of all ICU-admission diagnoses. 9e12 While cerebral toxoplasmosis remains a life-threatening CNS opportunistic infection, 13 neurological complications could also be explained by direct HIV effects on the CNS, even in patients receiving suppressive HAART, 14 or indirectly, by systemic conditions with CNS symptoms unrelated to HIV infection, HAART complications, 15,16 and/or by CNS immune-reconstitution syndromes.…”
Section: Introductionmentioning
confidence: 99%